Формирование теоретических знаний по физической культуре учащихся швейного производства в процессе профессионально-прикладной физической подготовки - Голованова, Наталия; Golovanova, Nataliya (Східноєвропейський національний університет імені Лесі Українки, 2015)
Теоретические знания является фундаментом познавательной деятельности и формирования мотивации к занятиям по физической культуре. В статье представлены способы формирования теоретических знаний по физической культуре учащихся швейного производства в процессе профессионально-прикладной физической подготовки. Определены методы обучения, представлены сфера внедрения и формы занятий. Рассмотрены особенности применения интерактивных методов обучения и инновационных средств контроля знаний, подробно описано использование перекрестных зачетов, применяемых в рамках формирования теоретических знаний по физической культуре учащихся швейного производства в процессе профессионально-прикладной физической подготовки. Theoretical knowledge is the foundation of cognitive activity and formation of physical training motivation. The article presents the methods of the theoretical knowledge formation on physical culture of garment production students in the process of professionally-applied physical preparation. The methods of training are determined, and the sphere of implementation and study forms are presented. There are considered the features of interactive teaching methods application and innovative means of knowledge control, and use of cross-tests used in the framework of theoretical knowledge formation on physical cultureamong garment production students in the process of professionally-applied physical preparation, are described in detail.
Physical Culture of Students of Garment Production in the Process of Professionally-applied Physical Preparation
Keywords: теоретические знания; комплексный подход; внедрение; учащиеся; швейное производство; theoretical knowledge; integrated approach; implementation; students; garment production